Review and Prospect of Tissue-agnostic Targeted Strategies in Anticancer Therapies - Peng, Yu; Tao, Hongxun; Gao, Yuanqing; Yang, Yuanyuan; Chen, Zhiyong (Current Topics in Medicinal Chemistry, 2021)
Due to the increasing prevalence of cancer year by year, and the complexity and refractory nature of the disease itself, it is required to constantly innovate the development of new cancer treatment schemes. At the same time, the understanding of cancers has deepened, from the use of chemotherapy regimens with high toxicity and side effects, to the popularity of targeted drugs with specific targets, to precise treatments based on tumor characteristics rather than traditional anatomical location classification. In precision medicine, in the view of the specific cancer diseases and their biological characteristics, there is a great potential to develop tissue-agnostic targeted therapy with broad-spectrum anticancer significance. The present review has discussed tissue-agnostic targeted therapy based on the biological and genetic characteristics of cancers, expounded its theoretical basis and strategies for drug development. In addition, the feasible drug targets, FDA-approved drugs, as well as drug candidates in clinical trials have also been summarized. In conclusion, the “tissue-agnostic targeted therapy” is a breakthrough in anticancer therapies.
Keywords: Cancers